Production chain of artisanal cachaça: the case of agroindustry producer of cachaça artisanal (Research, Society and Development, 2021)
This article aims to observe the production process of cachaça artisanal, the company's insertion in the municipality of Palestina de Goiás-GO and its market acceptance. The cachaça production chain is an economic sector that integrates several activities in a production chain. To support the analysis, bibliographic research was used to raise information about the cachaça production system, the methodology, therefore, characterized. as exploratory and explanatory of an applied nature, with a qualitative approach, collected through questionnaires, interviews, on-site visits and SWOT matrix find out potentially and bottleneck organization operational. The analysis of the results allows us to infer that the studied company promotes employability and income in the city, the company adopts a competitive strategy, depriving for the quality of the drink and direct marketing to the consumer.